2009
DOI: 10.1038/ng.305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in PCDH11X is associated with susceptibility to late-onset Alzheimer's disease

Abstract: By analyzing late onset Alzheimer's disease (LOAD) in a genome wide association study (313,504 SNPs, 3 series, 844 cases/1,255 controls) and evaluating the 25 SNPs with most significant allelic association in 4 additional series (1,547 cases/1,209 controls), we identified a SNP (rs5984894) on Xq21.3 in PCDH11X that is strongly associated with LOAD in American Caucasians. Analysis of rs5984894 by multivariable logistic regression adjusted for sex gave global P values of 5.7×10 -5 in stage I, 4.8×10 -6 in stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
192
2
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(199 citation statements)
references
References 17 publications
2
192
2
3
Order By: Relevance
“…In the second study, performed by our group, we failed to replicate this finding, although we did find an association between the C allele of rs8702 and increased P-tau 181 CSF levels in patients with incipient AD (Andersson et al 2007a). Several genome-wide association studies of AD have been reported but have not identified any association of KLC1 with AD (Coon et al 2007;Grupe et al 2007;Reiman et al 2007;Abraham et al 2008;Bertram et al 2008;Li et al 2008;Beecham et al 2009;Carrasquillo et al 2009;Harold et al 2009;Lambert et al 2009;Poduslo et al 2009;Potkin et al 2009). Altogether, the rather weak single SNP associations with AD in this and the previous study reporting association with KLC1, lack of association in the genome-wide association studies, the somewhat contradicting result of rs3212079, and the lack of strengthened association upon haplotype analysis, implies that the observed associations may be a result of type I error rather than a true association of KLC1 with AD.…”
Section: Discussioncontrasting
confidence: 69%
“…In the second study, performed by our group, we failed to replicate this finding, although we did find an association between the C allele of rs8702 and increased P-tau 181 CSF levels in patients with incipient AD (Andersson et al 2007a). Several genome-wide association studies of AD have been reported but have not identified any association of KLC1 with AD (Coon et al 2007;Grupe et al 2007;Reiman et al 2007;Abraham et al 2008;Bertram et al 2008;Li et al 2008;Beecham et al 2009;Carrasquillo et al 2009;Harold et al 2009;Lambert et al 2009;Poduslo et al 2009;Potkin et al 2009). Altogether, the rather weak single SNP associations with AD in this and the previous study reporting association with KLC1, lack of association in the genome-wide association studies, the somewhat contradicting result of rs3212079, and the lack of strengthened association upon haplotype analysis, implies that the observed associations may be a result of type I error rather than a true association of KLC1 with AD.…”
Section: Discussioncontrasting
confidence: 69%
“…The PCDH11X (protocadherin 11 X-linked) gene has scarcely been investigated; a polymorphism in this gene has been linked to Alzheimer disease (27,28). The TGIF2LX (TGFB-induced factor homeobox 2-like, X-linked) gene is associated with male infertility and may be required for the regulation of spermatogonial stem cell specification and proliferation, but its role in females is not clear (29).…”
Section: Resultsmentioning
confidence: 98%
“…Between 2007 and 2009, several genome-wide association studies (GWASs) in AD were performed with low numbers of cases and controls (less than 1000 per group), limiting their relevance for such a complex disease [11][12][13][14][15][16]. However, since then, several powerful GWASs have been recently published, suddenly improving our knowledge of the AD genetics.…”
Section: Introductionmentioning
confidence: 98%